Correlation between reforms and foreign debt in transition countries - Filipović, Sanja; Raspopović, Neda; Tošković, Jelena (Industrija, 2015)
After the global economic crisis escalated, transition countries indicated growth in their external debt. The aim of the paper is to determine the existence of a correlation between the transition reforms and the level of external debt. The research is based on applied Mann-Whitney U Test on a sample of 27 transition countries. Transition countries are divided into two groups depending on whether their value of the average transition indicator in 2012 is greater or less than 3.4. The research has shown a positive and statistically significant correlation between the observed variables, i.e. that countries with higher average transition indicator have a greater external indebtedness. The regression analysis has found a positive and statistically significant correlation between the observed variables in the case of Serbia that enters the zone of high indebtedness. The research findings indicate the need to review the efficiency of existing economic policies as well as to define new direction of development that would provide the impetus to the economic growth of transition countries without additional external debt.